Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/sc.2014.244
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetic resonance imaging in a naturally occurring canine model of spinal cord injury

Abstract: Study design: Retrospective cohort study. Objectives: To analyze magnetic resonance imaging (MRI) evaluator agreement in dogs with spinal cord injury (SCI) caused by intervertebral disk herniation (IVDH) using semiautomated and manual lesion segmentation and to analyze the associations between MRI and functional outcome. Setting: United States of America. Methods: T2-weighted MRIs from dogs with SCI resulting from thoracolumbar IVDH were identified from a database. Evaluators categorized MRIs on the basis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…These two ratios were not statistically significant between groups, possibly because cerebrospinal fluid signal loss and/or intramedullary hyperintensity could be underestimated or missed entirely on standard T2 sagittal images alone. Both qualitative and quantitative assessment of cerebrospinal fluid attenuation and intramedullary hyperintensity may have been more accurate if multiplanar images were evaluated in the current study, as was suggested by a recent report in which agreement for identification and measurement of intramedullary spinal cord lesions was better on T2 images in the transverse plane compared to the sagittal plane …”
Section: Discussion/conclusionmentioning
confidence: 53%
“…These two ratios were not statistically significant between groups, possibly because cerebrospinal fluid signal loss and/or intramedullary hyperintensity could be underestimated or missed entirely on standard T2 sagittal images alone. Both qualitative and quantitative assessment of cerebrospinal fluid attenuation and intramedullary hyperintensity may have been more accurate if multiplanar images were evaluated in the current study, as was suggested by a recent report in which agreement for identification and measurement of intramedullary spinal cord lesions was better on T2 images in the transverse plane compared to the sagittal plane …”
Section: Discussion/conclusionmentioning
confidence: 53%
“…For this study, dogs admitted to the Department of Small Animal Medicine and Surgery of the University of Veterinary Medicine Hannover between June 2013 and April 2015 were prospectively recruited. The dogs had to fulfill the following inclusion criteria: acute paraplegia (0-7 days since observed onset of clinical signs) or subacute paraplegia (8-28 days since onset of clinical signs), 23,37,38 SCI confined to the T3-L3 spinal cord segments and a body weight <20 kg. Onset of clinical signs was defined and recorded as the time point when owners noticed a nonambulatory state of their dog.…”
Section: Animalsmentioning
confidence: 99%
“…Identification of T2‐weighted intramedullary hyperintensities was performed upon assessment of sagittal images . Corresponding transverse T2‐weighted images were evaluated for detection of hyperintensities' length expansion to increase accuracy of measurements . T1‐weighted sequences were assessed in transverse planes to exclude presence of T1‐weighted hyperintensities .…”
Section: Methodsmentioning
confidence: 99%